The Myosin-V Myo51 and Alpha-Actinin Ain1p Cooperate during Contractile Ring Assembly and Disassembly in Fission Yeast Cytokinesis - Zoe L. Tyree; Kimberly Bellingham-Johnstun; Jessica Martinez-Baird; Caroline Laplante (Journal of Fungi, 2024)
Cytokinesis is driven in part by the constriction of a ring of actin filaments, myosin motors and other proteins. In fission yeast, three myosins contribute to cytokinesis including a Myosin-V Myo51. As Myosin-Vs typically carry cargo along actin filaments, the role of Myo51 in cytokinesis remains unclear. The previous work suggests that Myo51 may crosslink actin filaments. We hypothesized that if Myo51 crosslinks actin filaments, cells carrying double deletions of ain1, which encodes the crosslinker alpha-actinin, and myo51 (∆ain1 ∆myo51 cells) will exhibit more severe cytokinesis phenotypes than cells with the single ∆ain1 mutation. Contrary to our expectations, we found that the loss of Myo51 in ∆ain1 cells partially rescued the severity of the node clumping phenotype measured in ∆ain1 cells. Furthermore, we describe a normal process of contractile ring “shedding”, the appearance of fragments of ring material extending away from the contractile ring along the ingressing septum that occurs in the second half of constriction. We measured that ∆ain1 ∆myo51 cells exhibit premature and exaggerated shedding. Our work suggests that Myo51 is not a simple actin filament crosslinker. Instead, a role in effective node motion better recapitulates its function during ring assembly and disassembly.